In search of perfumes : a lifetime journey to the source of nature's scents - Roques, Dominique (HarperVia, 2023)
Do you know how many flowers it takes to produce a kilo of rose oil? One million roses, each handpicked. When it comes to nature, Dominique Roques is a unique authority. He has spent the last thirty years working closely with local communities across the globe to establish a sustainable supply of natural ingredients crucial to perfume making.